Study of the Electrical and Diffusion Barrier Properties in Ultrathin Carbon Film-Coated Copper Microwires for Interconnects - Chang, Chang-Shuo; Wang, Da-Jiun; Li, Tse-Chang; Shen, Chang-Hong; Jing, Yuan-Chou; Wu, Gien-Huang; Lin, Jen-Fin (Journal of materials engineering and performance, 2019)
Four specimen patterns with the microstructure of a microcopper wire are deposited on the Si-wafer substrate plus thermal oxide (SiO 2 ) film as the top layer. Each pattern was prepared to have two kinds of specimens, including with and without ultrathin carbon film between the copper wire and the top layer (SiO 2 ). The effect of carbon film on electrical properties is evaluated via the measurements of the I (current)– V (voltage) curve, sheet electrical resistance, current leakage, and its ratio and effective permittivity. A rapid thermal annealing (RTA) technique is provided as an economic and efficient method to grow the ultrathin carbon film rapidly as the interlayer. Appropriate choices of 900 °C and 3 min as the annealing temperature and time can produce ultrathin carbon film with nearly 100% coverage of the copper surface. The sheet resistance of specimen demonstrates the behavior exactly opposite to that of the carbon film coverage of wire surface. The combined effect of elevating the voltage and annealing temperature of the specimen with carbon film on the current leakage is much lower than that arising in the specimen without carbon film, so long as the carbon films operating at that temperature (between 350 and 500 °C) are still sustainable. The differences in current leakage and effective permittivity between these two kinds of specimen are significantly increased by raising the temperature. The intensity (IC) of copper diffusions into the SiO 2 layer in the specimens with the carbon film demonstrates behavior similar to that of current leakage (CL). The IC and CL values for the temperatures ≦ 350 °C are much lower than those obtained at 500 °C.